An overview of the high-resolution global LAnd surface satellite (Hi-GLASS) products suite - Shunlin Liang; Tao He; Jie Cheng; Bo Jiang; Huaan Jin; Ainong Li; Siwei Li; Liangyun Liu; Xiaobang Liu; Han Ma; Dan-Xia Song; Lin Sun; et al. (Science of Remote Sensing)
Numerous high-level satellite land products at kilometer scales have been widely used. There is an increasing need for high-resolution products to cater to different applications; however, very few such products exist. This demand has led to the development of the High-resolution Global LAnd Surface Satellite (Hi-GLASS) products suite. This paper presents an overview of the world's first suite of high-resolution products, which currently includes 15 instantaneous products (only clear pixels) at 30-m resolution generated from Landsat long-term data records. These products comprise cloud mask, aerosol optical depth, surface reflectance, surface albedo, net radiation, land surface temperature, leaf area index (LAI), fraction of absorbed photosynthetically active radiation (FAPAR), fractional vegetation cover, fractional forest cover, gross primary production (GPP), soil moisture, evapotranspiration (ET), normalized difference vegetation index (NDVI), and land cover dynamics. Although most of the algorithms have already been published in the literature, we have addressed the challenges of operational implementation to produce the suite of products. Additionally, this paper presents further product validation and intercomparisons with several existing regional products. While the goal is to generate these products globally starting from 1980s, currently, the products are mostly available over the United States and China from 2013 to 2022, as well as globally for 2015 and 2020. Besides land cover dynamics, five spatially seamless products (gap-filled for cloudy pixels) have been generated at a fixed temporal resolution (16 days) by integrating with the coarser-resolution GLASS products, such as albedo, LAI/FAPAR, fractional vegetation cover, and NDVI. We are currently working to generate all these Hi-GLASS products with global coverage and spatial continuity, as well as enhancing the spatial resolutions and increasing the number of Hi-GLASS products. The Hi-GLASS products will be freely downloaded at www.glass.hku.hk.